Inflammation and vasopressin hypersecretion in aging - Mutig, Kerim; Lebedeva, Svetlana; Singh, Prim B. (Frontiers in Endocrinology, 2025)
Low-grade inflammation, both hypothalamic and systemic, sensitizes the neuroendocrine response to osmotic stimuli whose proximate cause is chronic underhydration common in older adults due to diminished thirst perception. These events drive persistent vasopressin (VP) release. VP exerts antidiuretic effects via renal V2 receptors and functions as a stress hormone through widely expressed V1a and V1b receptors. These latter actions are central to inappropriate activation of the hypothalamic-pituitary-adrenal axis observed in aging, as VP stimulates secretion of the adrenocorticotropic hormone. The resulting sustained elevations in circulating VP and cortisol contribute to metabolic, renal, and cardiovascular disorders that compromise health and lifespan in older individuals. This review reconciles the concept of microinflammation with recent molecular insights into hypothalamic osmosensitivity, proposing a model for the maladaptive hypersecretion of vasopressin in advanced age. This framework may inform the development of targeted interventions to normalize VP secretion, thereby mitigating the metabolic, cardiovascular, and renal diseases that disproportionately affect older adults.